INOVASI PENGOLAHAN MINYAK KEMIRI SEBAGAI PENGGERAK EKONOMI KREATIF DESA - Jamu, Maria Endang; Langga, Lambertus; Sari, Santy Permata (LPPM Universitas Flores, 2025)
This community service aims to explore the potential of candlenut oil (Aleurites Moluccana) as a superior product in Ndetundora II Village, which has primarily utilised candlenut as a cooking ingredient. The methods employed include processing candlenut through roasting and pressing, where the nuts are heated without oil until they change color, then ground and pressed to extract the oil. The results indicate that candlenut oil offers various benefits, including promoting hair growth, reducing gray hair, and aiding in the healing of wounds and skin diseases, which can enhance the quality of life for the community. Additionally, socialisation and training on candlenut oil production are expected to enhance the skills and knowledge of the community, as well as expand market opportunities through social media. Recommendations for follow-up include developing marketing strategies and product diversification to boost the village's economy.